The Role of Celebrity Endorsement and Brand Love to Increase Purchase Intention in E-Commerce Companies - Aji, Dwi Kuncoro; Wikaningrum, Tri (Jurnal Akuntansi, Manajemen dan Ekonomi, 2025)
This study examines the effect of brand love on purchase intention, celebrity endorsement on purchase intention, celebrity endorsement on brand love, and the role of brand love as a mediator in the relationship between celebrity endorsement and purchase intention. The variables used include celebrity endorsement as an independent variable, purchase intention as a dependent variable, and brand love as a mediating variable. This study used a quantitative approach with SPSS 25 for data analysis. Sampling was carried out through a purposive sampling technique, and data were collected through a questionnaire with a Likert scale distributed online via Google Forms. The population of this study included all people in Semarang, Indonesia, with a sample of 100 respondents who were interested in shopping at Tokopedia. The results showed that brand love had a positive effect on purchase intention, celebrity endorsement had a positive effect on purchase intention, celebrity endorsement had a positive effect on brand love, and brand love can mediate the relationship between celebrity endorsement and purchase intention.